Evaluation of the CFS Program in Bekasi City Using the CIPP Model - Nurfajriah, Nurfajriah; Sutisna, Anan; Madani, Faisal (FKIP - Universitas Riau, 2025)
This study evaluates the implementation of the Child-Friendly School (CFS) program in Bekasi City using the CIPP model (Context, Input, Process, Product). Data were collected through interviews, field observations, and document analysis to capture the perspectives of principals, teachers, students, and parents. Findings show significant variations among schools. SDI Labschool STAI Bani Saleh achieved a mature implementation stage, with child-friendly principles fully internalized, participatory learning applied, and strong collaboration with parents and community stakeholders. SMPN 4 Bekasi was in a transitional phase, with partial teacher readiness and limited facilities, while MI At-Taqwa 28 remained at an initial stage, emphasizing socialization rather than practical application. Analysis indicates that low contextual and input readiness restricts the quality of processes and outcomes, whereas higher readiness supports inclusive practices and student well-being. This study provides practical recommendations for improving teacher capacity, school infrastructure, and stakeholder engagement, aiming to strengthen the sustainability and effectiveness of CFS programs in urban contexts. The results also offer guidance for policymakers and school administrators to enhance child-centered education practices in similar urban settings.